2018
DOI: 10.3390/jcm7100359
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient Is a Novel Imaging Biomarker of Myopathic Changes in Liver Cirrhosis

Abstract: Diffusion weighted imaging can provide information regarding tissue composition and can quantitatively characterize different pathological changes by means of apparent diffusion coefficient (ADC). The study comprised of 114 patients with liver cirrhosis—22 women and 92 men with a mean age of 56.5 ± 9.0 years. In all patients, the Model for End Stage-Liver Disease (MELD) score was calculated. Furthermore, 12 healthy persons (5 women, 7 men), mean age, 42.1 ± 16.2 years, were investigated as a control group. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…FFMA was independently associated with mortality. Surov et al [104] recently described higher apparent diffusion coefficient (ADC) values in cirrhosis compared to healthy people. ADC values significantly correlated with the severity of cirrhosis assessed by MELD score.…”
Section: Magnetic Resonance Imaging: a Non-radiating Equivalent To Ctmentioning
confidence: 99%
“…FFMA was independently associated with mortality. Surov et al [104] recently described higher apparent diffusion coefficient (ADC) values in cirrhosis compared to healthy people. ADC values significantly correlated with the severity of cirrhosis assessed by MELD score.…”
Section: Magnetic Resonance Imaging: a Non-radiating Equivalent To Ctmentioning
confidence: 99%
“…The study does not offer a direct proposal for the clinical use of the proposed indices in the assessment of sarcopenia. In the multivariate analysis, the authors also used only the MELD score[ 53 ].…”
Section: Diagnostic Methods In the Field Of Sarcopeniamentioning
confidence: 99%
“…Regarding the application of DWI for sarcopenia, Surov et al found a significant correlation between the model for end stage-liver disease and muscle changes in patients with cirrhosis, and even proposed the apparent diffusion coefficient (ADC) as new biomarker (74). Similarly, McPherson and colleagues identified significant differences in ADC values of the lower limb muscles between patients with spinal cord injury and healthy controls (75) (Figure 5).…”
Section: Dwimentioning
confidence: 99%
“…Aside from brain imaging, DWI's main field of application is oncological imaging (69)(70)(71). However, it can be also reliably used for musculoskeletal diseases including myositis and sarcopenia (46,(72)(73)(74). Indeed, in muscles, extra-, intra-, and transcellular water diffusion as well as capillary perfusion occur and the signal attenuation on DWI images is mainly due to the extracellular component and to microvascular perfusion (75).…”
Section: Dwimentioning
confidence: 99%